Relationship Between Metal Vapor in Arc and Droplet Transfer Mode in GMAW - Xian SUN (Taiyuan Ligong Daxue xuebao, 2022)
The relationship between metal vapor in arc and droplet transfer mode in GMAW was reviewed. The results show that when welding with high current and corresponding welding parameters and different shielding gases, the conductivity of the vapor in arc plasma center is different, resulting in different positions of current path, and finally leading to different (streaming, projected, and droplet) droplet transfer modes. The metal vapor reduces the electrical conductivity at the center of arc plasma, expands the current path in the arc, and the direction of the dominant force acting on droplet facilitates droplet transfer, which fully meets the formation conditions of droplet spray transfer. The effects of shielding gas type, arc temperature, and welding wire composition on metal vapor mainly depend on their effects on the electrical conductivity change of arc plasma. It is possible to regulate the droplet transfer phenomenon by controlling the conductivity of metal vapor to realize the spray transfer of pure CO2 shielding gas. Further research is needed on the key technologies.